2020
DOI: 10.1186/s12864-020-07293-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiles of sturgeon lateral line electroreceptor and mechanoreceptor during regeneration

Abstract: Background The electrosensory ampullary organs (AOs) and mechanosensory neuromasts (NMs) found in sturgeon and some other non-neopterygian fish or amphibians are both originated from lateral line placodes. However, these two sensory organs have characteristic morphological and physiological differences. The molecular mechanisms for the specification of AOs and NMs are not clearly understood. Results We sequenced the transcriptome for neomycin treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 61 publications
(82 reference statements)
0
19
0
Order By: Relevance
“…Conversely, the neuromast-enriched dataset (Wang et al, 2020) included Insm1, which we found in sterlet to be ampullary organrestricted. Furthermore, the 'common' dataset (Wang et al, 2020) included genes whose expression in sterlet and paddlefish was either ampullary organ-specific (e.g., the voltagegated K + channel genes Kcna5 and Kcnab3, as well as Neurod4; this study; Modrell et al, 2017a), or mechanosensory-specific (e.g., Foxg1 and Isl1; this study). Overall, we think that the stage 45 Siberian sturgeon tissue dissections (Wang et al, 2020) were unable to separate ampullary organs and neuromasts completely.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Conversely, the neuromast-enriched dataset (Wang et al, 2020) included Insm1, which we found in sterlet to be ampullary organrestricted. Furthermore, the 'common' dataset (Wang et al, 2020) included genes whose expression in sterlet and paddlefish was either ampullary organ-specific (e.g., the voltagegated K + channel genes Kcna5 and Kcnab3, as well as Neurod4; this study; Modrell et al, 2017a), or mechanosensory-specific (e.g., Foxg1 and Isl1; this study). Overall, we think that the stage 45 Siberian sturgeon tissue dissections (Wang et al, 2020) were unable to separate ampullary organs and neuromasts completely.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the 'common' dataset (Wang et al, 2020) included genes whose expression in sterlet and paddlefish was either ampullary organ-specific (e.g., the voltagegated K + channel genes Kcna5 and Kcnab3, as well as Neurod4; this study; Modrell et al, 2017a), or mechanosensory-specific (e.g., Foxg1 and Isl1; this study). Overall, we think that the stage 45 Siberian sturgeon tissue dissections (Wang et al, 2020) were unable to separate ampullary organs and neuromasts completely. Like our own stage 46 paddlefish lateral line organ-enriched dataset (Modrell et al, 2017a), the stage 45 Siberian sturgeon datasets are not exhaustive (Wang et al, 2020): some of the genes whose expression we have validated in stage 45-46 sterlet and/or paddlefish lateral line organs were missing (e.g., Satb2, Sox2 and Sox8; this study; Modrell et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations